Aquaculture Perspective of Multi-Use Sites in the Open Ocean The Untapped Potential for Marine Resources in the Anthropocene - Buck, Bela H.; Langan, Richard (Springer International Publishing : Imprint: Springer, 2017)
This book is open access under a CC BY 4.0 license. This volume addresses the potential for combining large-scale marine aquaculture of macroalgae, molluscs, crustaceans, and finfish, with offshore structures, primarily those associated with energy production, such as wind turbines and oil-drilling platforms. The volume offers a comprehensive overview and includes chapters on policy, science, engineering, and economic aspects to make this concept a reality. The compilation of chapters authored by internationally recognized researchers across the globe addresses the theoretical and practical aspects of multi-use, and presents case studies of research, development, and demonstration-scale installations in the US and EU. .